Current account adjustment and financial integration - Pascal Towbin (Graduate Institute of International and Development Studies, 2008)
The paper investigates whether higher financial integration leads in general to slower current account adjustments. The study estimates theoretically founded trade balance reaction functions for a panel of seventy countries from 1970-2004. The empirical analysis finds that adjustment in integrated economies is slower. Consistent with the presented theory the trade balance of integrated economies is more persistent, responds less strongly to net foreign assets, and is more sensitive to fluctuations in net output. A sufficiently strong response to net foreign assets is also a condition for external sustainability. Under high integration countries appear to stay close to the sustainability limit.
Keywords: F32; F36; F41; 330; current account adjustment; reaction function; financial integration; capital mobility; Finanzmarktregulierung; Leistungsbilanz; Kapitalmobilität; Reaktionsfunktion; Schätzung; Welt